Comparing the use of lexical bundles in Indonesian-English translation by student translators and professional translators - Hilda Novita; Deny A. Kwary (Translation and Interpreting : the International Journal of Translation and Interpreting Research, 2018)
Knowledge of lexical bundles is essential for translators, and the study of lexical bundles should be an integral part of translation training. This study investigated the lexical bundles made by student translators and professional translators in the Indonesian-English translation work. The student translators were sophomore students who had completed a translation course, while the professional translators were certified translators who were also members of Indonesian Translators Association. The findings of this study and the statistical calculations using Chi-square tests revealed that the group of professional translators produced a higher frequency and number of types of lexical bundles than the student translators did. This means that the frequency and the number of types of lexical bundles depended on the group of translators. This study also classifies the lexical bundles into the five functional categories described by Mahlberg (2007a). The classification shows a similarity in the number of functional categories the lexical bundles fitted into. However, the types of lexical bundles found within each category were significantly different. Consequently, we can conclude that the production of lexical bundles, even in translation, depends on the ESL proficiency level.